Pengaruh Pendidikan dan Pelatihan terhadap Prestasi Kerja Guru Melalui Motivasi Kerja - Kusnaini; Indra Prasetyo; C. Sri Hartati (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study is to describe Self Efficacy, Locus Of Control and The purpose of the authors of conducting this research was to describe and test and analyze the effect of education and training on teacher performance through motivation at the Office of the Regional Coordinator for Education and Culture, Rangsang District, Meranti Islands Regency. The research approach is included in the quantitative research approach. The population in this study were 54 teachers and the sample used in this study was 54 people. In this study the authors conducted a sampling using a census sampling technique. Methods of data collection with questionnaires and documentation. The data analysis technique used in this study uses Partial Least Square (PLS). Based on the results of the study, teacher performance, teacher motivation, education and training and teachers in the District Coordinator's Office for Education and Culture in Rangsang District, Meranti Islands Regency are in high condition, education and training has a significant effect on motivation, motivation has a significant effect on work performance Teachers, education and training have a significant effect on teacher performance. Education and training have a significant effect on teacher work performance, through motivation..